A scale for measuring teacher leadership in early childhood education in China: Development and validation. (July 2022) - Wang, Mo; Xia, Jing
This article describes the development of a teacher leadership scale (TLS) that can be utilized in early childhood education in China. A mixed methods research design was developed to meet the research aim, and both qualitative and quantitative data on the perceptions of teacher leadership from both middle leaders (i.e. vice-principal, key stage coordinator, subject leader) and classroom teachers were collected. In the qualitative study, semi-structured interviews with seven middle leaders and seven classroom teachers were conducted. The qualitative findings were then used for item pool generation in a quantitative study to create the TLS in four stages of development. The TLS questionnaire was distributed to 175 respondents and then to a further 419 respondents for exploratory factor analysis. The scale was further validated by confirmatory factor analysis with another 597 respondents. Its concurrent validity was also examined: teacher leadership was found to be positively associated with job satisfaction and the principal's authority openness. The article demonstrates that a four-factor model of teacher leadership as follows is psychometrically sound: (a) leading teaching and professional development; (b) characteristics of teacher leaders; (c) participating in school-wide decision-making; and (d) diversity and continuous improvement.